Gunung Kawi: Olahan Ketela Ungu Memberdayakan Masyarakat - Farida Nur Kumala; Muhammad Nur Hudha; Sudi Dul Aji (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2020)
Purple sweet potato Gunung Kawi is only sold raw, the price is very cheap. This causes the farmers to suffer losses. On the other hand, quite a lot of Wonosari Gunung Kawi residents become female migrant worker, because there are not enough producers in the village to meet the residents' needs. Based on that, the processing of purple sweet potato Gunung Kawi is needed to be developed into an effort that can absorb labor. The purpose of this service is to produce a purple sweet potato product business for residents of Wonosari Gunung Kawi. The service method used is through three stages, the first stage is preparation for coordination and outreach activities to partners. The second stage is implementation phase of training carried out training on the processing of purple sweet potato Gunung Kawi into several products such as sticks, bakpia and brownies from purple sweet potato of Gunung Kawi. The third stage is evaluation and assistance. The instruments in this service were interview sheets and activity observations. The results of the service show that the community has been able to produce and package products that are ready for sale and according to health standards.